Prepoznavnost in značilnosti besedja slovenskih protestantskih postil 16. stoletja - Merše, Majda (Slavistična revija, 2007)
Three extensive 16th-century Slovene Postils (Krelj 1567, Juričič 1567, and Trubar 1595) with a broad range of themes and with explication and illustation typical of this textual genre, created an oppurtunity for use of new lexicon not used outside Postils. The article surveys the scope of the newly used lexicon and its characteristics with respect to the thematic variety, derivational types, and idiosyncratic phonological features. In addition, it examines their dependency on the original texts.
Keywords: 16.st.; 16th cent.; besedne družine; izrazna sredstva; knjižni jezik; literary language; means of expression; new lexicon; novo besedje; Protestant postils; protestantske postile; Slovene language; slovenščina; word-families